Pengaruh Gaya Hidup, Harga, dan Kualitas Produk Terhadap Minat Beli Pakaian Bekas dalam Perspektif Ekonomi Syariah (Studi pada Masyarakat Kota Bengkulu) - Felisa Ayu Wulandari; Supardi Mursalin; Evan Stiawan (Universitas Muhammadiyah Surabaya, 2025)
This study aims to analyse the influence of lifestyle, price, and product quality on the purchase intention of secondhand clothing (thrifting) among the people of Bengkulu City from an Islamic economic perspective. This research employs a descriptive quatitative approach with data collected through questionnaires and processed using SPSS version 26. The population consists of Bengkulu City resident who have purchased secpndhand clothing at Panorama Market, with a sampel size of 100 respondentd. The data analysis tehniques include validity testing, reability testing, classical assumption test (normality, heteroscedascity, and multcollinearity tests) multiple linear regression analysis, and hypothesis testing (t-test, f-test, and R2 test). The result show that lifestyle has a significant effect on the intention to purchase secpndgand clothing, as indicated by a significance value of 0.000 (<0.05) and a t-value of 27.786. the higher the purchase intention. Price also has a significant influence, with a significance value of 0.000 (<0.05) and a t-value of 24.003, indicating that affordable and reasonable prices increase consumers’ purchase interest. Furthermore, product quality significantly affects the purchase of secondhand goods, as shown by a significance value of 0,000 (<0,05) and a t-value of 22.798. this implies that the better the quality offered, the higher the consumers’ buying interest.